2022
DOI: 10.1021/acs.jpcc.2c02196
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Designed Cluster–Surface Interaction for Halogen-like and Alkali-like Metal-Encapsulating Silicon Cage Superatoms on n- and p-Type Organic Substrates

Abstract: Metal-encapsulating Si 16 cage clusters (M@Si 16 ) are promising superatoms (SAs) for designing tunable properties for their assembled materials by changing the central metal atom: halogen-like, rare-gas-like, and alkali-like characteristics appear for the central metal atom of groups 3, 4, and 5, respectively. To fabricate SA assemblies, metal-encapsulating M@Si 16 SAs (M = Lu, Hf, and Ta) must be controllably immobilized on a substrate. Substrates decorated with organic molecules can facilitate optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…In fact, the chemical reactivity of halogen-like Lu@Si 16 against molecular oxygen is suppressed when it is deposited on HB-HBC to form Lu@Si 16 − HB-HBC + with satisfying 68 electron closure. 30 For the characterization of the behavior of M@Si 16 BCSAs on different kinds of substrate, Ta@Si 16 was deposited on strontium titanate (STO) as a representative of oxide substrate with step-by-step deposition. XPS measurement revealed that a layered film was formed.…”
Section: Intact Deposition Of Ncs and Their Application To Functional...mentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the chemical reactivity of halogen-like Lu@Si 16 against molecular oxygen is suppressed when it is deposited on HB-HBC to form Lu@Si 16 − HB-HBC + with satisfying 68 electron closure. 30 For the characterization of the behavior of M@Si 16 BCSAs on different kinds of substrate, Ta@Si 16 was deposited on strontium titanate (STO) as a representative of oxide substrate with step-by-step deposition. XPS measurement revealed that a layered film was formed.…”
Section: Intact Deposition Of Ncs and Their Application To Functional...mentioning
confidence: 99%
“…110 The CT complex formed between Ta@Si 16 and the C 60 molecular layer can be explained by considering the energetics for CT complexation. 30 Endothermic dissociation limits (DE) of Ta@Si 16 + C 60 À and Ta@Si 16 À C 60 + against the neutrals of M@Si 16 and C 60 can be calculated by the ionization energy and electron affinity of Ta@Si 16 and C 60 . The value of DE is smaller for Ta@Si 16 + C 60 À compared to Ta@Si 16 À C 60 + , which is consistent with the XPS results.…”
Section: Intact Deposition Of Ncs and Their Application To Functional...mentioning
confidence: 99%
See 3 more Smart Citations